Innovation and entrepreneurship : powerful tools for a modern knowledge-based economy /: powerful tools for a modern knowledge-based economy. (2015) - Al Mubaraki, Hanadi Mubarak; Muhammad, Ali Husain; Busler, Michael
No abstract available